Lactate and Pyruvate Are Major Sources of Energy for Stallion Sperm with Dose Effects on Mitochondrial Function, Motility, and ROS Production. Issue 2 (1st August 2016) - Darr, Christa R.; Varner, Dickson D.; Teague, Sheila; Cortopassi, Gino A.; Datta, Sandipan; Meyers, Stuart A.
Abstract: Stallion sperm rely primarily on oxidative phosphorylation for production of ATP used in sperm motility and metabolism. The objective of the study was to identify which substrates included in Biggers, Whitten, and Whittingham (BWW) media are key to optimal mitochondrial function through measurements of sperm motility parameters, mitochondrial oxygen consumption, and cellular reactive oxygen species (ROS) production. It was expected that mitochondrial substrates, pyruvate and lactate, would support sperm motility and mitochondrial function better than the glycolytic substrate, glucose, due to direct utilization within the mitochondria. Measurements were performed after incubation in modified BWW media with varying concentrations of lactate, pyruvate, and glucose. The effects of media and duration of incubation on sperm motility, ROS production, and oxygen consumption were determined using a linear mixed-effects model. Duplicate ejaculates from four stallions were used in three separate experiments to determine the effects of substrate availability and concentration on sperm motility and mitochondrial function and the relationship of oxygen consumption with cellular ROS production. The present results indicate that lactate and pyruvate are the most important sources of energy for stallion sperm motility and velocity, and elicit a dose-dependent response. Additionally, lactate and pyruvate are ideal for maximal mitochondrial function, as sperm in these media operate at a very high level of their bioenergetic capability due to the high rate of energy metabolism. Moreover, we found that addition of glucose to the media is not necessary for short-term storage of equine sperm, and may even result in reduction of mitochondrial function. Finally, we have confirmed that ROS production can be the result of mitochondrial dysfunction as well as intense mitochondrial activity.